The Roles of Public and National Development in Nigeria - Quadri, Razaq Femi; Ahmed, H. K. (POMLIF Journal of Library and Information Science, 2018)
The relevance of library and information services in the attainment of national development cannot be overemphasized. Public and national library libraries, as institutions saddled with the responsibility of catering for the information needs of the general public, play vital roles in the realization of these objectives. This paper takes a cursory look at the roles of public and national libraries in the promotion of national development in Nigeria; with emphasis on the educational, recreational, information and research-support services rendered in those libraries. Appropriate recommendations are made on how to improve the activities of those libraries.